Comprehensive multicultural education in the 21st century : increasing access in the age of retrenchment - Hinnant-Crawford, Brandi; Platt, C. Spencer; Newman, Christopher B.; Hilton, Adriel A. (Contemporary perspectives on access, equity, and achievement., 2019)
"The scholarship in this volume illustrates the state of multicultural education and articulates what educators committed to equity, inclusion, and a more just society must do to ensure the goals of multicultural education survive in the current age. The authors of these chapters bridge foundational knowledge with contemporary understandings; making the work both accessible for novices and beneficial for the authorities on multicultural education. With the diverse cast of contributors and topics ranging from mathematics instruction to discipline practices, this volume provides thoughtful discourse on issues of access: access to curricular content, access to opportunities to learn, as well as impediments to access. Containing chapters that speak to discipline specific pedagogical practices, the structures of schooling, teacher education, and research methodologies, the collected work encourages scholars and practitioners to not be discouraged in the age of retrenchment"--